Overseas Student Experience of Homesickness - Faridha, Erina Nur; Widiasih, Puti Archianti (Fakultas Psikologi Universitas Islam Negeri Maulana Malik Ibrahim, 2024)
Abstract: The pursuit of higher education in an alien environment can give rise to a number of novel experiences and opportunities, which may require additional adjustment efforts. Homesickness is a phenomenon commonly experienced by overseas students as they transition from a familiar environment to one that is foreign. Being separated from a familiar environment, which has constituted a part of one's life for an extended period, can give rise to a range of emotions, including sadness, anxiety, and homesickness. To meet the needs of international students, it is important to consider their psychological well-being, particularly in terms of social adjustment and self-acceptance. Identifying and addressing factors that contribute to homesickness is crucial. In this study, a qualitative approach with a phenomenological perspective was employed, and a purposive sampling technique was utilized. The data collection techniques employed in this study involved observation and interviews at Prof. Dr. HAMKA Muhammadiyah University over a period of approximately one month. Three overseas students from Java were interviewed, representing the regions of East Java, Central Java, and West Java. The results of this study provide an overview of the influence of psychological well-being and coping strategies applied by overseas students on homesickness experienced during overseas studies.